Effects of Moisture Stress Levels at Different Growth Stages on Nodulation and Nitrogen Fixation in Common Bean (Phaseolus Vulgaris L.) Genotype - Ndimbo, M. A; Nchimbi-Msolla, S; Semu, E (Asian Journal of Agriculture and Rural Development, 2015)
Moisture stress is among the limiting factors to crop yields. The objective of this study was to determine the effects of moisture stress imposed at different growth stages of bean plants on nodulation and nitrogen fixation. The experiment was conducted in greenhouse and in the field, at Sokoine University of Agriculture. The bean genotype “Kijivu” was used, the stages were; (i) VC (Cotyledonary and unifoliolate leaves visible), (ii) V2 (Second trifoliolate leaf unfolded), (iii) V4 (Fourth trifoliolates on the main stem, blossom clusters not opened) and (iv) R2 (Pods 1/2 inch long. Irrigation treatments were initiated to maintain moisture treatments of 100%, 75%, 50%, or 25% of the soils field capacity for each plant growth stage until plant maturity. Moisture stress significantly affected nodulation, nitrogen fixation, and finally grain yields. Numbers of nodules per plant were reduced by 56.0% in greenhouse and 69.2% in the field between V4 and VC at 25% moisture regime. Shoot biomass was reduced by 40.8% and 26.8% while root biomass was reduced 23.5% and 31.5% in greenhouse and field, respectively. These results suggest that for maximum nodulation and nitrogen fixation to be achieved, moisture stress must be avoided at the VC and V2 growing stages.